Characterizing The Biological Constituents Of Platelet-poor Plasma–do The Platelets Matter? A Prospective Cohort Study. Issue 7 (29th July 2019) - Mannava, Sandeep; Whitney, Kaitlyn E.; King, Jillian; Kennedy, Mitchell; Dornan, Grant; Chahla, Jorge; Evans, Thos A.; Huard, Johnny; Provencher, Matthew T.; LaPrade, Robert F.
Objectives: Platelet-rich plasma (PRP) is comprised of several biologically active factors that can stimulate musculoskeletal healing processes. The supernatant of PRP, known as PPP, is biologically active and may also stimulate tissue regeneration. In some instances, such as muscle injury, PPP may be preferred to PRP in order to stimulate muscle regrowth in a basic science study that was previously performed. Platelet poor plasma (PPP) is has several biologically active molecular factors that may be utilized to stimulate tissue healing. While platelet rich plasma has been previously studied and characterized, few studies have sought to quantify the biological constituents of PPP. The purpose of this study was to quantitate and assess growth factors, other chemokines, and cytokines in PPP derived from human peripheral blood that has been centrifuged. Study Design: Non-randomized, prospective cohort study; Level of evidence: 2. Methods: Peripheral blood was drawn to create PPP at three time points from sixteen healthy volunteers. Hematology analysis was conducted on the PPP to quantify the platelet fold-difference from baseline measurements. The PPP samples were immediately assayed and analyzed on the MagPix® following processing completion. Specific immunoassay kits used were human cytokine/chemokine magnetic bead panel, TGF-β magnetic bead panel, MMP magnetic bead panel 1, and MMP magnetic bead panel 2. Results: Among the biological factors tested, there was a significant positive association, defined by two factors being associated in that when one factor increases the other also increases, between BMI and the biological composition of PPP with PDGF AA, PDGF AB, MMP-1, MMP-9, MMP-13, and MMP-12 (p<0.05). Similarly, there was a significant positive association (p<0.05), between age and biological composition of PPP for MMP-9 and MMP-7. Conclusion: PPP has several biological factors, both anabolic and catabolic, that can potentially be utilized in musculoskeletal medicine to treat various conditions, such as muscle injury. PPP is biologically active and this study characterizes its anabolic and catabolic profile. These factors are influenced by certain demographic factors such as age and body mass index (BMI). Higher BMI significantly correlated to higher levels of PDGF AA, PDGF AB, MMP-1, MMP-9, MMP-13, and MMP-12 in PPP. This supernatant of the better-studied PRP is biological active and warrants further investigation for its therapeutic potential. Platelets could change the biological composition of plasma utilized for regenerative medicine applications, but this study demonstrates that the plasma alone has biological properties that may provide benefit in treating certain musculoskeletal conditions. This study will help clinicians better understand the biological nature of PPP and may aide in the more targeted use of PPP therapeutically.